THE EFFECTS OF WEBQUEST INTEGRATED WITH BIG SIX SKILLS ON INFORMATION LITERACY AND ANALYTICAL THINKING OF SAFETY ENGINEERING UNDERGRADUATES IN ENGINEERING MATHEMATICS SUBJECT - Sirisuk, Sasinapa; Jienmongkol, Seksan; Rattanakulwattana, Jamorn; Chakkhuean, Sunisa (Journal of Interdisciplinary Development (Humanities and Social Sciences), 2026)
This study aimed to: 1) develop and evaluate the efficiency of a WebQuest–Big Six Skills learning management plan for 2001101 Engineering Mathematics against the E1/E2 ≥75/75 criterion; 2) compare information-seeking skills of Safety Engineering students before and after instruction; 3) compare academic achievement; and 4) assess student satisfaction across three dimensions—task quality, process efficacy, and skill transfer to professional contexts. A purposive sample of 32 first-year Safety Engineering students from the Faculty of Engineering and Technology, Shinawatra University, enrolled in 2001101 Engineering Mathematics in the second semester of academic year 2026, participated. Research instruments comprised a WebQuest–Big Six Skills instructional plan, a 30-item achievement test, a 12-item satisfaction questionnaire, and a Search Log. Percentage, mean, and standard deviation were used for data analysis. Results revealed that the instructional plan attained an efficiency ratio of 75.83/76.77, exceeding the 75/75 benchmark. Post-instruction mean achievement (x̄ = 23.28) was higher than pre-instruction (x̄ = 22.19), and overall student satisfaction was at a high level (x̄ = 4.13, S.D. = 0.64).